2015
DOI: 10.1016/j.cub.2015.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Specification, and Plasticity of the Great Vessels of the Heart

Abstract: SUMMARY The pharyngeal arch arteries (PAAs) are a series of paired embryonic blood vessels that give rise to several major arteries that connect directly to the heart. During development, the PAAs emerge from nkx2.5-expressing mesodermal cells and connect the dorsal head vasculature to the outflow tract of the heart. Despite their central role in establishing the circulatory system, the embryonic origins of the PAA progenitors are only coarsely defined, and the factors that specify them and their regenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 50 publications
10
63
0
Order By: Relevance
“…We therefore performed whole mount immunohistochemistry using V5 tag-specific antibodies. Internally epitope tagged Tcf21 was readily detectable in an expression pattern consistent with the previously published mRNA expression pattern151718 (Fig. 4e,f).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We therefore performed whole mount immunohistochemistry using V5 tag-specific antibodies. Internally epitope tagged Tcf21 was readily detectable in an expression pattern consistent with the previously published mRNA expression pattern151718 (Fig. 4e,f).…”
Section: Resultssupporting
confidence: 87%
“…Second, at least five of the F1s positive for tag integration harbored frameshift mutations in the second copy of the gene. We proceeded to cross F1s heterozygous for tag integrations to each other as well as other F1 fish, and observed that in each of the crosses where both parents were heterozygous for a frameshift mutation, approximately 25% of the embryos displayed a branchial arch malformation phenotype consistent with the recently published tcf21 mutant18 and morphant17 phenotypes (Fig. 4b,d).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…However, lack of stat4 prevents proliferation of nkx2.5 + cells and eventually results in stenosis of the primitive GVs. A previous study showed that tcf21 , together with nkx2.5 , marked a group of PAA progenitor cells, but the tcf21 + nkx2.5 + progenitors were not required for PAA formation10. In this study, we found that genetic ablation of stat4 did not affect the tcf21 -expressing PAA cells.…”
Section: Discussionsupporting
confidence: 46%
“…Chromatin was immunoprecipitated using specific antibodies. Five primer pairs 1, 2, 3, 4, 5 were designed to cover the 1.6‐kb genomic region of the downstream enhancer. Results are shown as the fold enrichment of each protein in every genomic segment.…”
Section: Resultsmentioning
confidence: 99%